THE AESTHETIC COMPONENT OF INDEX OF ORTHODONTIC TREATMENT NEED (IOTN): A POPULATION BASED STUDY IN TWO HEALTH DISTRICT OF PUNJAB, PAKISTAN - Muhammad Azeem; Usman Shakoor; Altaf Ur Rehman et al. (Journal of University Medical & Dental College, 2018)
ABSTRACT:OBJECTIVE: The Index of Orthodontic Treatment Need (IOTN) was developed with aim to access treatment needs of orthodontic patients, and consisted of aesthetic component and the dental health component. The aim of current study was to apply aesthetic component of Index of Orthodontic treatment need in two local health districts of Punjab, Pakistan.MATERIAL & METHODS: In current cross sectional study, aesthetic component of index of orthodontic treatment need was applied using frontal intraoral photographs of 100 patients. The frontal pictures were compared with intraoral template photographs of aesthetic component of index of orthodontic treatment need, to ﬁnd out the orthodontic treatment need in Pakistani subjects. The data was collected and analyzed using SPSS 23.0. RESULTS: Results showed that 80 % of the subjects needed orthodontic treatment, out of which, 40% were female and 60% were male. Greater percentage of males was found in deﬁnite treatment need than females as per the aesthetic component of index of orthodontic treatment need. 20 % of the patients were classiﬁed as being in need of little/no treatment need. CONCLUSION: It was concluded that a high number of cases were in need of the orthodontic therapy as per the aesthetic component of index of orthodontic treatment need.